Determining who benefits most from cognitive rehabilitation for multiple sclerosis - Taylor, Lauren (2024)
Multiple sclerosis (MS) is a chronic inflammatory condition of the central nervous system characterised by lesions throughout the brain and spinal cord. Up to 70% of people with MS experience cognitive problems including difficulties with memory, attention, problem-solving, and language. These cognitive difficulties are debilitating and reduce the quality of life of people with MS and their families. Cognitive rehabilitation is a type of therapy that helps retrain cognitive skills. It is a specialised intervention that focuses on providing people with MS with the knowledge of and information about their cognitive difficulties, and in turn teaching them to use both internal and external aids to address them. This PhD project aimed to establish the effectiveness of cognitive rehabilitation for people with MS and understand which groups of people with MS are most likely to benefit from this intervention. This PhD involved three main studies.